2011
DOI: 10.5539/elt.v4n3p33
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Students in the EFL Classroom: A Case Study of Perspectives

Abstract: Motivating EFL students to develop in the target language is quite complex. In many cases, these students face difficulties in learning English and are often demotivated to learn. Research in classroom motivation has found that certain strategies can help these students adopt more positive attitudes and become more motivated in the learning process. This exploratory study investigates the perceptions through interviewing students and surveying teachers' views in an EFL Program of the problems that hinder these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 45 publications
5
44
0
1
Order By: Relevance
“…In a similar study conducted in Beirut, Lebanon, it appeared that the use of uninteresting materials, the lack of any new learning experience, and the ambiguous link between their current English courses and their future careers were among the major factors that hinder their motivation to learn English. The same study had also shown that when teachers use unique strategies that are tailor-fitted to the needs and personalities of their learners, students learn to adopt more positive attitudes towards learning the language (Bahous, 2011). Ultimately, the challenge is in initiating and maintaining young learners' interest in learning English, and studies have shown that one of the best ways to achieving such a goal is through extensive reading (Brown, 2000).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…In a similar study conducted in Beirut, Lebanon, it appeared that the use of uninteresting materials, the lack of any new learning experience, and the ambiguous link between their current English courses and their future careers were among the major factors that hinder their motivation to learn English. The same study had also shown that when teachers use unique strategies that are tailor-fitted to the needs and personalities of their learners, students learn to adopt more positive attitudes towards learning the language (Bahous, 2011). Ultimately, the challenge is in initiating and maintaining young learners' interest in learning English, and studies have shown that one of the best ways to achieving such a goal is through extensive reading (Brown, 2000).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…11, No. 7;2017 between students. Those events which match students' needs produce motivated students, who in term do better in language acquisition.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…11, No. 7;2017 Kurdistan. A questionnaire has been developed to explore the most effective factors of motivation for Kurdish EFL students as well as the impact of the motivation component of social support on other motivation factors.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations